Impact of Brand Personality on the consumer behaviour and its implications for the Marketer - Anchal Aggarwal*, Renu, (International Journal of Scientific Research and Management (IJSRM), 2017)
In this modern competitive environment, so many brands are available for the consumers to choose, all of which provide similar kind of benefits. So it is very important to differentiate our offerings from those of the competitors.in this context brand personality plays an important role to identify and differentiate our product. Brand personality can be defined as the set of personality traits of human which are attributed to a brand. In current scenario brand personality is very important for the companies to position their brand in the market.So in this study we highlight the Significance of brand personality for the consumer and marketer. For this purpose, we first take into account the literature review written on the topic, then we study the relationship of brand personality with the personality of the consumer, after that we study the impact of brand personality on the consumer behaviour with the help of a small questionnaire. It was concluded that brand personality has positive impact upon, the attitude of the consumers towards the brand, brand loyalty, brand satisfaction and brand attachment.On the basis of results of the questionnaire suggestions are given to the marketer regarding positioning of brand in the market and formulating advertising and promotional policies for the brand.